Penerapan Metode Multi-Attribute Utility Theory (MAUT) pada Pemilihan Broadcasting Terbaik - Karya Suhada; Saludin Saludin; Abdurrahman Sadikin; Indah Kusuma Dewi; Fifto Nugroho (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
In an increasingly sophisticated era and increasingly modern life, entertaining content makes Broadcasting a promising job field. This resulted in many people being interested in broadcasting. Broadcasting is a job related to broadcasting. All parties who participate in broadcasting, both cameramen, presenters, content creators, writer creators and so on. Broadcasting is usually useful for those who want to upload videos to YouTube, Tiktok, Instagram and so on. Broadcasting selection is done manually, it will take a long time and a lot of effort. Therefore a decision support system is needed in order to assist interested parties in choosing the best Broadcasting. In using a decision support system using this ranking method, the method used is the Multi-Attribute Utility Theory (MAUT) method. Based on the calculation results from the MAUT method, a result of 0.6731 is obtained with the alternative A7 On behalf of Bintang Simanjuntak as the best alternative that deserves to be accepted as Broadcasting.